Tracing Current Wildlife Trade: An Initial Investigation in Makassar City, Indonesia - Maulany, Risma Illa; Mutmainnah, Aisyah; Nasri, Nasri; Achmad, Amran; Ngakan, Putu Oka (Forestry Faculty, Universitas Hasanuddin, 2021)
Wildlife trade has become one of the main causes of species loss and extinction. Increasing anthropogenic pressure posits crucial challenges to wildlife, and several species are threatened or at the edge of extinction. In this study, we aimed to examine the current wildlife trade in Makassar City of South Sulawesi, especially focusing on traded species, their area of origin, price, conservation status and traders’ distribution across the city. We conducted a market survey and direct observations of animals and wildlife traders in several locations, using a questionnaire targeting both wildlife/pet sellers and buyers. We also interviewed government bodies related with wildlife trade. Our results showed that there were 13 distribution spots of wildlife trading in the city of Makassar, and 27 different wildlife suppliers. During the seven months of observation (March-September 2018), the trade involved 62 species of birds, mammals and reptiles. More than 50% of these species had Indonesian origins, and 18% were endemic species of Sulawesi Island. The highest number of animals traded in the market were birds. Out of the 2,642 individuals being traded, 32 were considered as protected species under the IUCN regulation, 24 were species whose trade is regulated by CITES, and 10 were nationally protected according to the Indonesian Government’s Laws. The traded animals were obtained from different sources, including direct hunters, middlemen, opportunists, and breeders, mostly from Sulawesi (44.19%) and western parts of Indonesia (37.21%).